Outcome of Submuscular Dynamic Compression Plates in Pediatric Subtrochanteric Fracture in a Tertiary Hospital - Morshed, Taufiq; Matin, Asraf ul; Umam, Shafiul; Bhuiyan, Mizanur Rahman; Roy, Liton Kumar; Bhuya, Muhammed Shahed Anwar; Monjur ul Alam, Muhammad; Moniruzzaman, Mohammad (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Femur subtrochanteric fractures are not common in paediatric patients. Several therapeutic approaches have been used with adults and children. The submuscular technique using Dynamic Compression Plates (DCP) is a minimally invasive approach that aims to provide stable fixation while minimizing soft tissue disruption. Methods: This is a retrospective study at the Orthopaedic Department at Comilla Medical College Hospital. All the pediatric subtrochanteric fracture patients operated with submuscular DCP at the Orthopaedic Department at Comilla Medical College Hospital between January 2022 to December 2023. Results: We had operated a total of 22 pediatric subtrochanteric fracture with submuscular small DCP. Flynn score was improved significantly after 12 months where 17 children were excellent category and 4 were satisfactory. Only one child had poor functional outcome. All the children were poor according to Beaty score. After 1-year, overall criteria were excellent in 18 cases. Rest 4 children were in satisfactory category. Conclusion: Submuscular DCP emerges as a reliable option, particularly in cases where conservative management or other surgical approaches may be less feasible. J Com Med Col Teachers’ Asso Jan 2025; 29(1): 08-14